Antenatal care service satisfaction and associated factors among pregnant women at public health facilities of Wogera district, Northwest Ethiopia: a cross-sectional study - Belachew, Asrat Kassaw; Debie, Ayal; Geberu, Demiss Mulatu; Dagnew, Abinet; Bitew, Gedamnesh; Dejene, Tadesse Mamo; Walle, Agmasie Damtew (Frontiers in Global Women's Health, 2024)
Background Pregnant women's satisfaction with Ante-Natal Care (ANC) is crucial for improving its quality and providing standardized healthcare services. However, studies on pregnant women's satisfaction with antenatal care and associated factors are limited in Ethiopia, particularly in the study area. Therefore, this study aimed to assess satisfaction and associated factors among pregnant women receiving antenatal care in Wogera district. Methods A facility-based cross-sectional study was conducted in Wogera district from March to April 2024. A total of 458 pregnant women who attended ANC at health facilities were included in the study. Interviewer -administered structured questionnaire was used to obtain the necessary information for this study and systematic random sampling was used to select the study participants. Multivariable and binary logistic regression analysis was used to identify the effect of each independent variable on the outcome (satisfaction). Results The overall satisfaction of antenatal care services among pregnant women was 92.1% (95% CI: 89.5, 94.5%). The majority (98.3%) of them were satisfied by the provider's greeting and 97.8% were satisfied by the cost of service but pregnant women were less satisfied by waiting time to see the health workers, cleanness of the toilet, and water supply. Satisfaction of pregnant women was associated with housewife occupational status [AOR = 3.05, 95% CI: 1.02, 9.15], civil servants occupational status [AOR = 4.02, 95% CI: 1.02, 15.85], age ≥25 [AOR = 2.78, 95% CI: 1.05, 1.74], advice on family planning [AOR = 7.29, 95% CI: 3.08, 17.05], one ANC visit [AOR = 3.61, 95% CI: 1.84, 8.74] and the respondents pregnant women who have ≥2 pregnancy [AOR = 4.55, 95% CI: 1.88, 11.03] were the predictors of level of satisfaction. Conclusion Pregnant women's satisfaction with antenatal care was high, influenced by factors such as having two or more pregnancies, timing of the first ANC visit, family planning advice, age ≥25 years, and being a housewife or civil servant. Efforts should focus on reducing wait times, ensuring clean water access, and improving latrine hygiene at healthcare facilities to sustain this satisfaction. Specifically, facilities should streamline appointments, maintain safe drinking water sources, and upgrade toilets for better comfort and hygiene.